International capital markets with time-varying preferences - Giuliano Curatola; Ilya Dergunov (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2017)
We propose a 2-country asset-pricing model where agents' preferences change endogenously as a function of the popularity of internationally traded goods. We determine the effect of the time-variation of preferences on equity markets, consumption and portfolio choices. When agents are more sensitive to the popularity of domestic consumption goods, the local stock market reacts more strongly to the preferences of local agents than to the preferences of foreign agents. Therefore, home bias arises because home-country stock represents a better investment opportunity for hedging against future fluctuations in preferences. We test our model and find that preference evolution is a plausible driver of key macroeconomic variables and stock returns.
urn:nbn:de:hebis:30:3-437482
Keywords: D51; D52; D53; E20; E21; F21; G11; G12; 330; asset pricing; general equilibrium; heterogeneous agents; interdependent preferences; portfolio choice